Effects of acromegaly treatment on left ventricular systolic function assessed by speckle tracking echocardiography in relation to sex differences: results from a prospective single center study - Popielarz-Grygalewicz, Agata; Stelmachowska-Banaś, Maria; Raczkiewicz, Dorota; Czajka-Oraniec, Izabella; Zieliński, Grzegorz; Kochman, Wacław; Dąbrowski, Marek; Zgliczyński, Wojciech (Frontiers in Endocrinology, 2023)
Background Despite the preserved LVEF, patients with acromegaly are characterized by subclinical systolic dysfunction i.e., abnormal global longitudinal strain (GLS) assessed by speckle tracking echocardiography (STE). The effect of acromegaly treatment on LV systolic function assessed by STE, has not been evaluated so far. Patients and methods Thirty two naïve acromegalic patients without detectable heart disease were enrolled in a prospective, single-center study. 2D-Echocardiography and STE were performed at diagnosis, 3&6 months on preoperative somatostatin receptor ligand (SRL) treatment and 3 months after transsphenoidal surgery(TSS). Results Treatment with SRL resulted in reduction in median (IQR) GH&IGF-1 levels after 3 months, from 9.1(3.2-21.9) to 1.8(0.9-5.2) ng/mL (p<0.001) and from 3.2(2.3-4.3) to 1.5(1.1-2.5) xULN (p<0.001), respectively. Biochemical control on SRL was achieved in 25.8% of patients after 6 months and complete surgical remission was achieved in 41.7% of patients. TSS resulted in decrease in median (IQR) IGF-1 compared to IGF-1 levels on SRL treatment: from 1.5(1.2-2.5) to 1.3(1.0-1.6) xULN (p=0.003). Females had lower IGF-1 levels at baseline, on SRL and after TSS compared to males. The median end diastolic and end systolic left ventricle volumes were normal. Almost half of the patients (46.9%) had increased LVMi, however the median value of LVMi was normal in both sex groups: 99g/m2 in males and 94g/m2 in females. Most patients (78.1%) had increased LAVi and the median value was 41.8mL/m2. At baseline 50% of patients, mostly men (62.5% vs. 37.5%) had GLS values higher than -20%. There was a positive correlation between baseline GLS and BMI r=0.446 (p=0.011) and BSA r=0.411 (p=0.019). The median GLS significantly improved after 3 months of SRL treatment compared to baseline: -20.4% vs. -20.0% (p=0.045). The median GLS was lower in patients with surgical remission compared to patients with elevated GH&IGF-1 levels: -22.5% vs. -19.8% (p=0.029). There was a positive correlation between GLS and IGF-1 levels after TSS r=0.570 (p=0.007). Conclusions The greatest beneficial effect of acromegaly treatment on LV systolic function is visible already after 3 months of preoperative SRL treatment, especially in women. Patients with surgical remission have better GLS compared to patients with persistent acromegaly.